Effect of Adding Fenugreek Seeds to the Ration on Milk Yield and Composition in Awassi Sheep (Journal of Hama University, 2022)
The research was conducted at the Agricultural Scientific Research Center in Hama. 15 Awassi sheep with an average age of 4 years old and an average body weight of (66) kg were used, close together in the date of giving birth, weaning of their lambs and milk production in the previous productive season, with an average of 263 kg milk/season. and they were divided into three groups (5 sheep per group) that were fed for 60 days on a diet with a similar level of crude protein and energy with a difference in the proportions of fenugreek seeds (0-3-6) %, in compliance to the appropriate nutritional rating for the age and productivity stage (NRC, 1985), milk production was recorded and the chemical composition of the milk was analyzed (protein - fat - lactose - non-fat solids - milk density).The results showed an increase in the daily and total milk production of the groups to which fenugreek seeds were added in comparison with the control. Adding fenugreek seeds led to a significant (P